Information seeking behavior of foreign students of the University of the Philippines Diliman - Reyes, Rico Marco B. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
Information seeking behavior has been the focus of inquiry within the Library and Information Science communities in the past decades. Earlier studies included user (demographics) and use studies for improving collection development. These were followed by studies that explored the research practices of individuals or groups to design appropriate systems and services to aid those habits. It was in the last decade when user studies evolved into the examination of information seeking behavior employing more holistic approaches (Tibbo, 2004). This study determined the information-seeking behaviors of foreign students of the University of the Philippines Diliman. This relates to how foreign students start to locate information materials, what methods they usually do to locate information needed and what information materials are found useful to them. The study also focused on finding out the relationships between certain factors that the information-seeking behavior of foreign students in terms of their success in finding the needed information in the library.